Development of TPACK Self-Assessment Instrument for Madrasah Ibtidaiyah Preservice Teachers - Annur, Aan Fadia; Jaeni, Muhamad; Musthofa, Musthofa; Musa, Muhammad Maskur (FONDATIA, 2024)
The digital era requires teachers to have TPACK abilities. Not only teachers, but pre-service teachers also need to be equipped with TPACK abilities in order to become competitive teachers in the digital age. To measure the TPACK ability of prospective teachers, it is necessary to develop an instrument that can measure TPACK. This research was conducted with the aim of developing a TPACK self-assessment instrument for PGMI students who are prospective teachers of Madrasah Ibtidaiyah (MI). The approach used in this research is research and development (R&D) type ADDIE, which is carried out through five (5) stages, namely analysis, design, development, implementation, and evaluation. The instrument was developed based on the seven components of TPACK. A total of 34 PGMI students who have carried out teaching practices act as samples in this study. After validation and reliability tests were carried out using SPSS, 39 items were valid statements out of a total of 40 items, with an alpha coefficient of 0.970. Thus, it can be said that 39 items of statements are reliable and appropriate to be used to measure the TPACK ability of PGMI students.